Importance of new approaches in education for higher education institutions - Zoran Ivanovic; Ace Milenkovski (UTMS Journal of Economics, 2019)
Education is the main driver of the development of science and economic development, but it can also be defined as an essential process in acquiring knowledge, skills and competencies. Purpose of this research paper was to highlight the needs and demands of modern society in preparing human resources for labour market with adequate skills and competences. During this process educational system has a great role in achieving this goal. Due to dynamic and developing environment many countries in the south-eastern Europe find very hard to adapt those changes. In this research paper several different approaches to education and learning process were presented and in detail explained. Learning through information processing, through research, simulation, and application of other interactive teaching methods using information and communication technology (ITC) should be imposed on the traditional form of ex cathedra. Education system in various south-eastern European countries was analysed and the research results suggest that south-eastern European countries have below average results compared to those from EU countries, but there is enough space to progress especially through the use of computer-based technologies. Today, the implementation of computer-based technologies has become a necessity in achieving greater engagement of students.
Keywords: I21; I23; I25; 330; higher educational system; distance learning; knowledge; professional development; labour market